Dermatological manifestations in endocrine disorders - Ostrovski-Sauberlich,Cael (2024)
Abstract This article reviews the dermatological manifestations that frequently arise in endocrine disorders, encompassing conditions such as diabetes mellitus, acromegaly, polycystic ovary syndrome, hypothyroidism, Addison’s disease, among others. It explores the interactions between the endocrine system and the skin, highlighting how hormonal imbalances can result in a variety of skin symptoms. With a comprehensive approach, it offers important clinical insights for dermatologists and endocrinologists, aiming at a better understanding and an accurate diagnosis of these conditions.